“Getting into dance”: aesthetic-corporeal knowledge in the rapper's songs Rincon Sapiência (PerCursos, 2021)
This article aims to reflect briefly on the meanings of the songs of São Paulo rapper Rincon Sapiência. Especially, the content of the songs present in his most recent work Mundo Manicongo: Dramas, Danças e Afroreps. The proposed analysis to be undertaken here aims to identify the cultural and pedagogical contribution that this record has, when we think about the prism of black corporeality and the identity re-significations of the subjects belonging to this group. In this way, besides evidencing the impact of Rincon's songs in the construction of contemporary black identities, we also seek to point out the historical conceptions about black sociabilities. In which many of the cultural manifestations exercised by the black population had, and still have, as the main vector of expression the black body added to musicality.
Keywords: Rincon Sapiência; black corporeity; black identity